Sociodemographic and clinical factors associated with caregivers’ satisfaction in a tertiary pediatric hospital - Concha-Gutiérrez, Carolina; Rivas-Riveros, Edith; Espinoza-Quiroz, Pilar; Palmeiro-Silva, Yasna K. (Revista Chilena de Salud Pública, 2020)
Introduction: Assuring the quality of care and patient safety are central pillars of health sys¬tems, in order to respect patients’ dignity and autonomy. On the basis of these principles, healthcare systems should consider users’ personal characteristics to evaluate their satisfaction with services; however, most user satisfaction surveys only ask about general issues, such as infrastructure and wait times. The objective of this study was to evaluate socio-demographic and clinical factors related to parent/caregiver’s user satisfaction in a tertiary pediatric hospital located in Santiago, Chile. Materials and Methods: The Pediatric Acute Care questionnaire was adapted and applied to 304 parents/caregivers. Psychometric characteristics were evaluated, and a generalized linear model was applied to obtain socio-demographic and clinical factors related to the user satis¬faction score. Results: Parents/caregivers who perceive their child’s health as ‘good’ obtained, on average, 4.64 more satisfaction points than those who consider their child’s health as ‘bad’ (IC95% 0.9 – 8.38; p=0.015). Likewise, as a child’s age increases by one month, satisfaction increases by 0.0026 points (IC95% 0.01 – 0.041; p=0.001). Nonetheless, each additional day a child is hospitalized decreases user satisfaction by 0.06 points (IC95% -0.69 – -0.003; p=0.034), holding other variables constant. Discussion: User satisfaction is associated with parents/caregivers’ personal characteristics. Health workers should consider these characteristics in order to deliver better care, adjusted to their users’ needs.